Nanomedicine & Nanotoxicology Future Could Be Reshaped Post-COVID-19 Pandemic - Al-Ahmady, Zahraa S.; Ali-Boucetta, Hanene (Frontiers in Nanotechnology, 2020)
Since its first emergence in December 2019, the coronavirus-2 infection has quickly spread around the world and the severity of the pandemic has already re-shaped our lives. This review highlights the role of nanotechnology in the fight against this pandemic with a focus on thedesign of effective nano-basedprevention and treatment options that overcome the limitations associated with conventional vaccines and other therapies. How nanotechnology could be utilised to understand the pathology of the ongoing pandemic is also discussed as well as how our knowledge about SARS-COV-2 cellular uptake and toxicity could influence future nanotoxicological considerations and nanomedicine design of safe yet effective nanomaterials.